The Origin of Human Mesenchymal Stromal Cells Dictates Their Reparative Properties. Issue 5 (30th September 2013) - Naftali‐Shani, Nili; Itzhaki‐Alfia, Ayelet; Landa‐Rouben, Natalie; Kain, David; Holbova, Radka; Adutler‐Lieber, Shimrit; Molotski, Natali; Asher, Elad; Grupper, Avishay; Millet, Eran; Tessone, Ariel; Winkler, Eyal; et al.
Abstract : Background: Human mesenchymal stromal cells (hMSCs) from adipose cardiac tissue have attracted considerable interest in regard to cell‐based therapies. We aimed to test the hypothesis that hMSCs from the heart and epicardial fat would be better cells for infarct repair. Methods and Results: We isolated and grew hMSCs from patients with ischemic heart disease from 4 locations: epicardial fat, pericardial fat, subcutaneous fat, and the right atrium. Significantly, hMSCs from the right atrium and epicardial fat secreted the highest amounts of trophic and inflammatory cytokines, while hMSCs from pericardial and subcutaneous fat secreted the lowest. Relative expression of inflammation‐ and fibrosis‐related genes was considerably higher in hMSCs from the right atrium and epicardial fat than in subcutaneous fat hMSCs. To determine the functional effects of hMSCs, we allocated rats to hMSC transplantation 7 days after myocardial infarction. Atrial hMSCs induced greatest infarct vascularization as well as highest inflammation score 27 days after transplantation. Surprisingly, cardiac dysfunction was worst after transplantation of hMSCs from atrium and epicardial fat and minimal after transplantation of hMSCs from subcutaneous fat. These findings were confirmed by using hMSC transplantation in immunocompromised mice after myocardial infarction. Notably, there was a correlation between tumor necrosis factor‐α secretion from hMSCs and posttransplantation left ventricular remodeling and dysfunction. Conclusions: Because of their proinflammatory properties, hMSCs from the right atrium and epicardial fat of cardiac patients could impair heart function after myocardial infarction. Our findings might be relevant to autologous mesenchymal stromal cell therapy and development and progression of ischemic heart disease.